1992
DOI: 10.1182/blood.v79.8.2135.2135
|View full text |Cite
|
Sign up to set email alerts
|

Diverse point mutations result in glucose-6-phosphate dehydrogenase (G6PD) polymorphism in Taiwan

Abstract: Glucose-6-PHOSPHATE dehydrogenase (G6PD; EC 1.1.1.49) deficiency is the most common human enzymopathy, affecting more than 200 million people worldwide. Although greater than 400 variants have been described based on clinical and biochemical criteria, little is known about the molecular basis of these G6PD deficiencies. Recently, the gene that encodes human G6PD has been cloned and sequenced, which enables us to examine directly the heterogeneity of G6PD at the DNA level. During the past 10 years, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This observation supports previous publications suggesting Southern Chinese have distinctive genetic characteristics from that of the Northern Chinese. Studies on glucose-6-phosphate dehydrogenase deficiency, Thalassemia and debrisoquin hydroxylation phenotype have reported the finding of genetic variation amongst Chinese subjects from different regions (Wang et al, 1993;Tang et al, 1992;Tang et al, 1993;Liu et al, 1997). Tang et al 1999 have also identified a recurrent BRCA1 mutation 589-590delCT related to early onset breast cancer in 3 unrelated patients of Southern Chinese origin.…”
Section: Resultsmentioning
confidence: 99%
“…This observation supports previous publications suggesting Southern Chinese have distinctive genetic characteristics from that of the Northern Chinese. Studies on glucose-6-phosphate dehydrogenase deficiency, Thalassemia and debrisoquin hydroxylation phenotype have reported the finding of genetic variation amongst Chinese subjects from different regions (Wang et al, 1993;Tang et al, 1992;Tang et al, 1993;Liu et al, 1997). Tang et al 1999 have also identified a recurrent BRCA1 mutation 589-590delCT related to early onset breast cancer in 3 unrelated patients of Southern Chinese origin.…”
Section: Resultsmentioning
confidence: 99%
“…In order to study polymorphic markers relevant to the Asian setting (1311C>T [18] and IVSXI C93T [19] , Table 1 ), in all samples with 563C>T and a subset of samples wild-type at C563, PCR and sequencing of exons 11 and 12 including introns 11 and 12 was undertaken using the protocol of Tang et al [20] ; the forward primer was GAAGCCGGGCATGTTCTTCAAC and the reverse CCAGGGCTCAGAGCTTGTG . All amplification fragments spanning exons 11 and 12 were subjected to gel electrophoresis and purified using FavorPrep™ GEL/PCR Purification kit (Favorgen, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…The recent advances in techniques have allowed an accurate molecular characterization of the G6PD gene and a number of variants have been identified (Beutler, 1991). The abnormalities for G6PD deficiency have also extended to ethnic groups in Asia, China (Chang et al, 1992;Tang et al, 1992;Chiu et al, 1993;Lo et al, 1994;Xu et al, 1995;Ainoon et al, 1999), Taiwan (Tang et al, 1995), Indonesia (Soemantri et al, 1995), and Southeast Asia (Iwai et al, 2001). There are reports for population-based studies on G6PD heterogeneity in Middle East.…”
Section: S U M M a R Ymentioning
confidence: 99%